Surface Encounters : Thinking with Animals and Art. - Broglio, Ron, 1966- (Posthumanities., 2011)
What it is like to be an animal? Ron Broglio wants to know from the inside, from underneath the fur and feathers. In examining this question, he bypasses the perspectives of biology or natural history to explore how one can construct an animal phenomenology, to think and feel as an animal other--or any other. Until now phenomenology has grappled with how humans are embedded in their world. According to philosophical tradition, animals do not practice the self-reflexive thought that provides humans with depth of being. Without human interiority, philosophers have believed, animals live on the sur.